(untitled) (Al-Qamar, 2021)
The principles of Takfīr internally reflect the legislative conscienceless. In these principles the ingredients of īmān are determined in a manner that in case of denial one does not remain as mu’min. This has nothing to do with what relates with heart; as it is purely a legal domain. But the matter of Takfīr cannot firmly be devoid of heart-related injunctions because it means negation of īmān that is a heart-relating matter. To ensure the balance between Takfīr having ostensible and legislative feature, and īmān, that relates with heart, is a complex point where one among ẓāhir (ostensible) and bāṭin (internal) seems to be overcoming the other. The principles of Takfīr basically attempt to determine those foundations and underpinnings of Islam, the denial of which identify kufr (disbelief) that persists within the heart. By this way the matters of īmān, that are in fact heart-relating ones, could be brought with the domain of ostensible legislation. Most often, because of ta’wīl, the principles of Takfīr become lose that gives rise to the dilemma of abuse of those principles. Then, crossing over the legislative boundaries these principles adapt some other aspects. The social aspect among those different aspects is very significant without which, the tradition of the application of Takfīr may not be understood fully. In terms of application, Takfīr deos not remain solely an academic-legal activity. Here the need is felt that Takfīr should be discussed from various, and of course new, dimensions having the history thereof taken into account so that the tradition of Takfīr may be given a new and appropriate dimension on the basis of fresh and principled study.